A safety and pharmacodynamics study of temelimab, an antipathogenic human endogenous retrovirus type W envelope monoclonal antibody, in patients with type 1 diabetes. Issue 7 (12th March 2020) - Curtin, Francois; Champion, Bernard; Davoren, Peter; Duke, Sally; Ekinci, Elif I.; Gilfillan, Chris; Morbey, Claire; Nathow, Thomas; O'Moore‐Sullivan, Trisha; O'Neal, David; Roberts, Adam; Stranks, Stephen; et al.
Abstract: Aim: To report the first study of temelimab, a monoclonal antibody neutralizing the pathogenic human endogenous retrovirus type W envelope, in patients with type 1 diabetes (T1D). Materials and Methods: This double‐blind, placebo‐controlled, randomized clinical trial recruited adult patients with T1D within 4 years postdiagnosis and remaining C‐peptide secretion. Sixty‐four patients were randomized (2:1) to monthly temelimab 6 mg/kg or placebo during 24 weeks followed by a 24‐week, open‐label extension, during which all patients received temelimab. The primary objective was the safety and tolerability of temelimab. The secondary objective was to assess the pharmacodynamics response such as C‐peptide levels, insulin use, HbA1c, hypoglycaemia and autoantibodies. Results: Temelimab was well tolerated without any group difference in the frequency or severity of adverse events. Concerning exploratory endpoints, there was no difference in the levels of C‐peptide, insulin use or HbA1c between treatment groups at weeks 24 and 48. The frequency of hypoglycaemia events was reduced with temelimab ( P = 0.0004) at week 24 and the level of anti‐insulin antibodies was lower with temelimab ( P < 0.01); the other autoantibodies did not differ between groups. Conclusions: Temelimab appeared safe in patients with T1D. Pharmacodynamics signals (hypoglycaemia and anti‐insulin antibodies) under temelimab were observed. Markers of β‐cell functions were not modified by treatment. These results need to be further explored in younger patients with T1D with earlier disease onset.